Posição socioeconômica no curso de vida, mobilidade social e incidência de hipertensão arterial em participantes do ELSA-BRASIL - Jose Aparecido Soares Lopes (2020)
Hypertension is the leading modifiable risk factor for cardiovascular disease, contributing to about 10.5 million deaths or 19% of global deaths annually. It affects more heavily low and middle income countries, being its prevalence in Brazil in 2013 equal to 32.3%. The etiology of hypertension is complex and involves genetic, behavioral and psychosocial factors. Low socioeconomic position (SEP) at different stages of the life cycle has been consistently associated with higher incidence and prevalence of hypertension, which makes life course epidemiology an important approach to study and understand further this association, especially in countries marked by profound socioeconomic inequities such as Brazil. However, most studies performed so far were cross-sectional and few have investigated simultaneously SEP indicators for the three life cycle periods (childhood, youth and adulthood). Similarly, very few studies on SEP and HA have tested the accumulation of risk and socio-occupational mobility models. The aim of this dissertation was to investigate whether life course SEP (childhood, youth and adulthood) is associated with the incidence of hypertension in adults participating in ELSA-Brasil between the study first and second visits. Specifically, we verified whether the accumulation of exposure to low SEP throughout the life cycle and having adverse intra- and intergenerational socio-occupational mobility were associated with an increased risk of hypertension. This is a longitudinal study of participants of the Longitudinal Study of Adult Health (ELSA-Brasil), a cohort of 15,105 civil servants aged 35 to 74 years from six Brazilian states. All participants at the study baseline (2008 and 2010) who were free from hypertension, and attended the second study visit (2012-2014) were eligible to participate. Individual with incomplete or absent data on hypertension and SEP at both visits were excluded. Thus, the final sample consisted of 8,485 hypertension-free individuals at baseline who met the inclusion criteria. The response variable was incident hypertension at the 2nd visit defined as systolic blood pressure (BP) ≥ 140 mmHg and/or diastolic BP ≥ 90 mmHg and/or use of antihypertensive medication. The explanatory variables of interest were SEP indicators in childhood, youth and adulthood. Age, sex and race/skin color were regarded as confounders. We used the binomial logistic regression model and the magnitude of association was assessed by Odds Ratio (OR) and 95% confidence interval (95% CI). After adjustments for covariates, the following factors were associated with higher risk of hypertension: childhood SEP [mother's schooling - incomplete elementary education (OR: 1.25 95% CI: 1.06-1.47) and never studied (OR: 1, 28 95% CI: 1.02-1.60)]; youth SEP [middle (OR: 1.33 95% CI: 1.09-1.63) and low (OR: 1.21 95% CI: 1.02-1.44) occupational social class of the household head]; adulthood SEP [participant`s high school (OR: 1.44 95% CI: 1.26-1.66) and complete elementary education (OR: 1.41 95% CI: 1.08-1.82)], participant`s current middle (OR: 1.19 95% CI: 1.02-1.40); and low (OR: 1.51 95% CI: 1.27-1.79) occupational social class]. In addition, higher accumulation of low SEP (OR: 1.64 95% CI: 1.31-2.05), and having low stable intragenerational trajectory (OR: 1.51 95% CI: 1.25-1.81), descending (OR: 1.33 95% CI: 1.03-1.73) and low stable (OR: 1.37 95% CI: 1.14-1.65) intergenerational trajectories also increased the risk of hypertension. Our findings showed that exposures to low SEP in any phase of life cycle (childhood, youth and adulthood), as well as the accumulation of low SEP throughout life and presenting a descending or stable low SEP trajectories increase the risk of hypertension in about four years of follow up. Results suggest that longer exposure to adverse SEP throughout the life cycle, expressed by the accumulation of risk, is associated with greater risk of developing hypertension than the exposure over a specific period of time. Thus, in order to prevent and mitigate the impact of hypertension on adult health, public policies aimed at promoting opportunities and reducing socioeconomic inequalities should cover all life cycle periods, especially in countries such as Brazil where the burden of HA and social inequalities are greatest .